2009
DOI: 10.21161/mjm.13508
|View full text |Cite
|
Sign up to set email alerts
|

Siderophoregenic Acinetobacter calcoaceticus isolated from wheat rhizosphere with strong PGPR activity

Abstract: Thirty-two bacterial isolates were obtained from wheat rhizosphere in black cotton soils of North Maharashtra region and subsequently tested for in-vitro siderophore production. Wheat isolate SCW1, being a strong siderophore producer, was selected, identified and confirmed as Acinetobacter calcoaceticus. The strain produced catechol type of siderophores during exponential phase which was influenced by iron content of medium. Seed bacterization with siderophoregenic A. calcoaceticus improved plant growth in pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Except for direct mechanisms, PGPR are still able to promote plant growth by indirect mechanisms such as siderophore production and phosphate solubilization. Some PGPR, such as Acinetobacter calcoaceticus , produces siderophores and can grow in iron‐free media . Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Except for direct mechanisms, PGPR are still able to promote plant growth by indirect mechanisms such as siderophore production and phosphate solubilization. Some PGPR, such as Acinetobacter calcoaceticus , produces siderophores and can grow in iron‐free media . Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, as these supernatants were rich in siderophores, it is possible that the antagonistic activity was at least partially generated by these molecules. Prashant et al ( 2009 ) demonstrated the antifungal activity of catechol-like siderophores from Acinetobacter calcoaceticus strain SCW1 against Aspergillus flavus , Aspergillus niger , Colletotrichum capsicum , and F. oxysporum . Sayyed and Reddy ( 2011 ) reported the growth inhibitory potential of siderophore-rich cell-free supernatants obtained from Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…isolates ( Kwon and Song, 2014 ). It has been reported that Acinetobacter calcoaceticus displays IAA and siderophore production that promotes wheat plant growth, with antagonistic activity to different phytopathogens such as Fusarium oxysporum , Aspergillus flavus and A. niger ( Sarode Prashant et al, 2009 ). Bacillus thuringiensis isolate has also been reported to promote growth in Abelmoschus esculentus plants by phosphate solubilization ( Bandopadhyay, 2020 ).…”
Section: Discussionmentioning
confidence: 99%